Softening Behaviour of Indonesian Wood Species - Wahyu Dwianto; Ikuho Iida; Kazuya Minato (Wood Research Journal, 2015)
This paper deals with softening behaviour measurements of Indonesian wood species by static bending tests. Wood samples with a size of 110mm (R) x 10mm (T) x 4mm (L) were bending tested in air-dry at 20°C and 65% relative humidity (RH), in water saturation at 20°C, and in water saturation at 80°C to know the decreasing of modulus of elasticity (MOE) and modulus of rupture (MOR) due to moisture content (MC) and both moisture content and temperature (MCT) changes. The wood samples represented Randu (Bombax ceiba. L) as the lowest specific gravity, i.e. 0.27 to Lamtoro (Leucaena glauca (Willd) Benth) as the highest specific gravity, i.e. 0.81. The three-point static bending test was carried out by a mechanical testing machine with a load capacity of 100kgf, loading deflection speed of 5mm/min, a span distance of 80mm at a room with a temperature of 20°C and 65% RH for air-dry wood samples, and that for wet wood samples were conducted in a water bath at 20°C (change in MC) and 80°C (change in MCT), respectively. MOE and MOR increased linearly with specific gravity regardless of wood species. On the other hand, maximum deflection did not correlate with specific gravity for any MCT conditions. The relative MOE and MOR which were calculated in wet 20°C to air-dry were affected from hardly to strongly depending on the wood species. Meanwhile, they decreased extremely when saturated in water at 80°C regardless of wood species. The relative MOE and MOR due to the change in MC or MCT was independent of specific gravity, as well. Furthermore, chemical compositions of the wood species were analysed to clarify the main factors that affected the decreasing of MOE and MOR due to MC and MCT changes. The results showed that the percentage of lignin and hemicelluloses in each wood played an important role in decreasing the static bending properties. Relative MOE and MOR decreased with increasing lignin and hemicellulose contents. It can be concluded that the hygrothermal properties of lignin and hemicelluloses significantly affect the changes of elastic and strength properties of wood in softening conditions.